Approach to reduce PAPR in Orthogonal Frequency Division Multiplexing Technique - et. al., Sakir Ahmed Mondal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Orthogonal Frequency Division Multiplexing (OFDM) is an efficient and attractive modulation technique that can be considered as the heart of all major wireless communication applications used as well as in development today. OFDM is an advanced version of Frequency Division Multiplexing (FDM) technique that separates the channel bandwidth into multiple narrow sub-bands in order to transfer information. With the progress of advance communication field there should be high data rate along with power efficiency and lower Bit Error Rate (BER). Due to advent of Internet of Things (IoT), Artificial Intelligence (AI), 5G and other network demanding technologies network congesting scenarios are becoming common and because of interfering channels noise is observed caused by adjacency of communicating devices. So, the fulfillment of current as well as future demand of high data rate and greater power efficiency are very much essential. These requirements are achieved very well with OFDM technique but at the cost of high Peak to Average Power Ratio (PAPR). High PAPR leads to in band distortion and Out of Band radiation along with power inefficiency while using practical power amplifier at the transmitter. This paper presents a review of OFDM and analysis of a technique for PAPR reduction. Additionally, the scopes and challenges in PAPR reduction have been documented which describes clipping technique to reduce PAPR through MATLAB simulation models.